Students’ learning obstacles and didactical anticipation in learning the Pythagorean theorem - Sandra, Yuce; Suryadi, Didi (Proceedings of International Conference on Research in Education, 2025)
The Pythagorean Theorem represents a fundamental concept in mathematics education, especially in its application to solving mathematical problems. However, in reality, many students continue to struggle with understanding the concept, resulting in significant learning obstacles. This study aims to investigate the learning obstacles faced by students in learning the Pythagorean Theorem. The study involved 28 eighth-grade students from a junior high school in Riau Province. This study adopts a qualitative design with a case study approach. Data collection was conducted through interviews, written tests, and observations. Data analysis was performed through reduction, presentation, and conclusion. Findings from this study indicate that students faced epistemological obstacles in learning the Pythagorean Theorem, particularly regarding their understanding of key concepts, such as a misunderstanding of the relationship between sides of a right triangle. Ontogenic obstacles were associated with students’ lack of learning readiness, particularly their insufficient understanding of triangle-related concepts that serve as foundational knowledge. Didactic obstacles were linked to how the material was presented, such as a lack of visual exploration related to presenting the meaning of the Pythagorean Theorem. The learning obstacles experienced by students help teachers anticipate future learning and outline several didactical anticipations that teachers should consider implementing.